Hypothesis: when is a seminoma not a seminoma?. Issue 2 (February 1981) - Raghavan, D; Heyderman, E; Monaghan, P; Gibbs, J; Ruoslahti, E; Peckham, M J; Neville, A M
Abstract : A xenograft line, HX 53, has been established in immune-suppressed mice from a specimen of a lymph node metastasis in a patient with a histological diagnosis of seminoma but with markedly raised circulating levels of alpha-fetoprotein. Histological, immunocytochemical, and ultrastructural studies of this xenograft line have suggested that a solid variant of yolk sac carcinoma may exist, which morphologically resembles seminoma, or that a continuum of differentiation exists between seminoma and yolk sac carcinoma.